Approaches to phyllodes tumour of the breast: a review article - Mohd Firdaus Mohd Hayati; Ho, Hui Lian; Nornazirah Azizan; Aishath Azna Ali; Zainal Adwin Zainal Abidin; Muhamad Aznan Suhaili (Medip Academy, 2017)
Phyllodes tumours are rare entities of fibroepithelial diseases. The exact pathogenesis and their relationship with fibroadenomas are oblivious. Women aged between 35 to 55 years are commonly affected, even younger in Asian population. Triple assessment should be applied as a guide to management in any breast pathology. Clinical appearances are typically diagnostic for phyllodes tumours. Even though sometimes inconclusive, mammography and ultrasonography are the main imaging modalities. Although the role of cytology is debatable, presence of both epithelial and stromal elements supports the diagnosis especially in malignant type. Core biopsy is rather favored in view of higher accuracy for the diagnosis. Accurate preoperative assessment and histologic diagnosis allow correct surgical intervention and subsequent avoidance of reoperation. Surgical management can be either wide excision with more than 1 cm margins or mastectomy without axillary surgery. Local recurrence has been associated with inadequate excision of the pseudopod. Adjuvant radiotherapy is recommended for positive surgical margin and for local control of borderline and malignant phyllodes tumors. The role of chemotherapy and endocrine therapy has not been fully studied.